2003
DOI: 10.2307/3558537
|View full text |Cite
|
Sign up to set email alerts
|

'The Girl in Question': A New Text from Roman London

Abstract: he text published here was found in 1994 during excavation at 1 Poultry in the City of London (TQ 3258 8110), on the north side of the main east-west road of Roman London just west of the Walbrook stream, in a layer of debris which postdated the destruction of a roadside building in a late Flavian fire. 1 It is only the second stilus-tablet 'page' from London to have been read almost in full. 2 It is a formal and formulaic text but, to a modern reader, its legal language makes this human document still more di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Londinium in particular is known to have experienced significant socioeconomic fluctuations over its centuries of occupation (Perring, ). Furthermore, Romano‐British populations are considered to have been diverse as a consequence of migration and in terms of social identities (Millett, 1995; Tomlin, ; Mattingly, ; Leach et al, ; Lewis, ; Eckardt et al, ). These features may drive heterogeneity in environmental experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Londinium in particular is known to have experienced significant socioeconomic fluctuations over its centuries of occupation (Perring, ). Furthermore, Romano‐British populations are considered to have been diverse as a consequence of migration and in terms of social identities (Millett, 1995; Tomlin, ; Mattingly, ; Leach et al, ; Lewis, ; Eckardt et al, ). These features may drive heterogeneity in environmental experience.…”
Section: Discussionmentioning
confidence: 99%
“…These features may drive heterogeneity in environmental experience. Particular evidence exists for social diversity and for migration in Londinium , including the presence of child‐migrants, whether free or enslaved, with a writing tablet from Londinium detailing the sale of an enslaved girl from Gaul (Perring, ; Tomlin, ; Gowland and Redfern, ; Millard et al, ). The Londinium cemeteries from which the adolescents of this study derive exhibit a variety of funerary practices that likely relate to such social and ethnic identities (Hall, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the imperial household this sense was extended into a grade or title often applied to imperial slaves who exercised a delegated financial authority especially in the provinces (Weaver 1972, 200–11). Such a uicarius called Vegetus is attested by a writing-tablet from London (Tomlin 2003), and we have suggested that after manumission he became the Cocceius Vegetus who receives 352 (see Tab . Vindol .…”
Section: The Textsmentioning
confidence: 97%
“…The archaeology of Londinium has revealed primary source evidence for children, such as the famous writing tablet detailing the sale of Fortunata, a Gaulish slave girl (Tomlin, 1993), as well as a limited number of funerary inscriptions, such as that of 15 year old Marcus Aurelius Eucarpus (Tomlin, et al, 2009, RIB 10), and a fragment of a sculpture depicting a small child holding a ball. Numerous children's leather shoes have also been recovered, which is unsurprising as leatherworking was an important industry in the settlement, and two small leather bikini briefs, possibly worn by children (Wilmott, 1982, Keily, 2011.…”
Section: The Children Of Londiniummentioning
confidence: 99%